Penerapan Konsep Sanitasi Standar Guna Menunjang Usaha Pengolahan Di Poklahsar Berkah Gawi Hapakat Kota Palangka Raya - Rosana Elvince (Jurnal Pengabdi, 2022)
This activity has been done in collaboration with Kelompok Pengolah dan Pemasar (Poklahsar) Berkah Gawi Hapakat. Food processed product produced by the group are abon ikan gabus, abon ikan patin, amplang ikan tenggiri, stik ikan pipih, empek-empek and otak-otak ikan tenggiri. As a new group, Poklahsar Berkah Gawi Hapakat needs assistance in the application of standard sanitation concepts, especially food, water, equipment, worker and environmental sanitations to obtain products that are safe for consumption and in accordance with food safety quality standards. In this activity, assistance was carried out by applying the concept of standard sanitation through the dissemination of the sanitation activity to obtain products that are in accordance with consumer demands and food safety quality assurance standards. The response of the group to this activity is quite positive because they share knowledge about sanitation which can affect the products produced and can attract consumers because raw materials to products are handled by taking into account good processing standards (Good Manufacturing Practices/GMP). Especially during the COVID-19 pandemic, many products are marketed by online, or through social media.